GCEC 2017 Proceedings of the 1st Global Civil Engineering Conference - Pradhan, Biswajeet; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book gathers the proceedings of the 1st Global Civil Engineering Conference, GCEC 2017, held in Kuala Lumpur, Malaysia, on July 25-28, 2017. It highlights how state-of-the-art techniques and tools in various disciplines of Civil Engineering are being applied to solve real-world problems. The book presents interdisciplinary research, experimental and/or theoretical studies yielding new insights that will advance civil engineering methods. The scope of the book spans the following areas: Structural, Water Resources, Geotechnical, Construction, Transportation Engineering and Geospatial Engineering applications.
Influence of polyethylene and stainless-steel fibers on compressive and tensile behavior of High Performance Fiber Reinforced Cementitious Composites -- RC column repaired with HPFRCC and confined with CFRP: numerical analyses to evaluate the column section capacity -- Overall Significance's Rank of Leadership Factors Amongst Critical Success Factors for Construction Projects -- Comparative Study on Change Orders in Building Projects -- Numerical Modeling for Twin Horizontal Circle Tunnels under Static and Dynamic Loads -- Critical Crack-Tip Opening Displacement of SCLC -- Glass Footbridge -- The Use of Polystyrene as Substitute of Sand in Pontoon Concrete -- Probabilistic analysis of slopes by finite element method -- Study of vehicle-bridgecoupled vibration using MATLAB/ Simulink -- Climate Change-Causes, Impacts, Mitigation: A Review -- Frontier in Three-Dimensional Cave Reconstruction - 3D Meshing Versus Textured Rendering -- Contributions of dry and wet weather runoffs to annual pollutant loading in tropical urban catchments.
Keywords: Civil engineering; Geotechnical engineering; Geographic information systems; Water; Hydrology; Climatology; Computer vision; Civil Engineering; Geotechnical Engineering and Applied Earth Sciences; Geographical Information System; Water; Climate Sciences; Computer Vision